Behavioral Manifestations Among Children with Autism Spectrum Disorder in Gharyan and their Differences According to the Gender Variable from the Teachers' Perspective - Fadwa Ali Kharwat; Howida Alhashmi Almassr (Journal of Scientific and Human Dimensions, 2026)
Autism Spectrum Disorder (ASD) is one of the most complex developmental disorders affecting a child's behavioral aspects and leading to social withdrawal. This study aimed to identify the behavioral manifestations of children with ASD from the perspective of their teachers in the city of Gharyan, Libya, while also examining differences based on the gender variable. The researchers adopted a descriptive-comparative approach, and the study sample consisted of 16 children (8 boys and 8 girls). A questionnaire on behavioral manifestations, adapted for the Libyan context, was administered as the primary research tool. The study yielded several results, most notably the prevalence of behavioral manifestations among children with ASD from the teachers' perspective, with cognitive-perceptual manifestations being more common than social ones. Additionally, the results showed no statistically significant differences in behavioral manifestations between male and female children. The study concluded with recommendations to enhance social and communication skills and develop cognitive perceptions through specialized educational programs.
Keywords: Behavioral manifestations; Autism Spectrum Disorder; Gharyan, Teachers' perspective; Gender variable